ANALISIS PSIKOLOGIS KOMPARATIF PENDEKATAN PEMBELAJARAN KI HADJAR DEWANTARA DAN BENJAMIN S. BLOOM - Idrus L. (Didaktika : Jurnal Kependidikan, 2019)
Ki Hadjar Dewantara and Benjamin S. Bloom have different learning approach in term of psychological aspect in learning activities. Ki Hajar Dewantara tends to maximize the  potency of each individual i.e. (educate the head, the heart, and the hand) and the social-cultural totality in interacting with the environment with "sistem among: care and dedication based on love. In another hand, Benjamin S. Bloom emphasizes on behaviorism theory which believes that learning is an internal process includes memory, retention, information process, energy and other psychological aspects. From  the character learning, Ki Hajar Dewantara focuses on attitude of students, how they communicate, humanism, and the physical aspect of student. It integrates the art and cultural aspect in learning process while Benjamin S. Bloom streghtening the cognitive aspect of student by implementing behaviorism learning process.